Welfare institutions, resources, and political learning. Interacting with the State as an Incentive for the Political Participation of Long-Term Unemployed Youth - Jasmine Lorenzini (Coordinamento SIBA, 2015)
This paper examines the impact of interactions with welfare institutions on the political partici-pation of long-term unemployed youth in two cities. We assess the role of resource redistribution and of political learning on engagement in protest activities. We use a unique dataset of long-term unemployed youth to predict the probability that long-term unemployed youth participate in protest activities and be-come politically alienated as a result of their interactions with the state. Our study suggests that the impact of staid aid on political participation comes from providing services through the unemployment office and the social aid office rather than from direct payments. However, we do not find strong evidence revealing a process of political learning, as political alienation does not seem to mediate the effect of interactions with the state on protest. The most important finding of our study is that the connection between welfare insti-tutions and political learning is context-dependent. We find a differential effect of interactions with the unemployment office and with the social aid office across cities.